Desempenho de cordeiras em pastagens cultivadas de inverno e verão sob níveis de suplemento - Elejalde, Denise Adelaide Gomes (2007)
This study was conducted to evaluate the performance of female lambs in cultivated pasture, with or without supply of supplement. Evaluated the performance of female lambs in cultivated pasture, Italian ryegrass (Lolium multiflorum Lam.) and Pearl millet more Alexandergrass (Urochloa plantagínea), in two experiments. In both the experiments the animals were submitted to following supplement levels: SS - animals exclusively in cultivated pasture; S.5; S1.0 e S1.5 - animals in cultivated pasture receiving supplement on proportion of .5; 1.0 and 1.5% of body weight (BW), respectively. The animals were supplemented daily with commercial rations in experiments 1 and 2, the rations presented 16.3 and 19.8% of CP; 25.8 and 19.7% of NDF, respectively. The supplemented female lambs with 0.5 and 1.5% of BW on Italian ryegrass pasture present greater average daily weight gain. The AWG in Italian ryegrass pasture was similar to receipt levels of supplement and superior no supplemented. The forage intake more supplement, CP and TDN intake, ADG, BSC and AWG were superior to supplemented female lambs in Pearl millet more Alexandergrass. Supplement of levels between 0.5 and 1.5% of BW, provide weight and body condition score of female lambs being mate on nine months of age with 70.2% of adult weight